Respond of the Growth and Production of Local Upland Rice Cultivars Sultra to the WateringVolume - Moizes dos R. Borromeu; Sadimantara, I gusti R.; Pasalon, Yulius B. (MultiTech Publisher, 2024)
The study aimed to investigate the growth and production of local upland rice Sultras based on watering volume. It was conducted in a 4x10 m greenhouse from April to August 2015, testing four cultivations of upland rice Sultra. The experiment involved four factors: water level (W1), cultivars (V1), (V2), (V3), and (V4). The parameters observed included plant height, tiller number, leaf number, dry weight, root weight, productive tiller number, days to flowering, weight of 1000 rice, grain per tiller, empty grain per tiller, blossoming age, and number of dry grain per tree. The results showed that water volume, cultivars, and water conditions significantly influenced the growth and production of upland rice Sultras. Water volume 100% (W3) resulted in good results for grain per tree, root dry weight, and fruiting time. Water conditions 25% (W1) and cultivar pae Uba (V2) showed the longest average grain to blossom. The study also found that cultivars Pae Uba (V2) and Pae Bou (V3) had good results for grain weight, productive tiller, seed weight, and grain per tree.